PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. BANK PERMATA CABANG SUNTER ROYAL - Yulidayanti; Arief Rachmawan Assegaf (Jurnal Ekonomi dan Industri, 2022)
Purpose to find out and analyze the work environment and work discipline simultaneously on the performance of employees of PT Bank Permata Sunter Royal branch. The research method of data collection used in this study is a descriptive method using a quantitative approach. The analytical method used is validity test, reliability test, classical assumption test, and hypothesis testing. There is a positive and significant influence, both partially and simultaneously, the work environment and work discipline on employee performance